Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1093/brain/awn199
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pain processing in chronic tension-type headache: a high-density EEG brain mapping study

Abstract: Central sensitization caused by prolonged nociceptive input from muscles is considered to play an important role for chronification of tension-type headache. In the present study we used a new high-density EEG brain mapping technique to investigate spatiotemporal aspects of brain activity in response to muscle pain in 19 patients with chronic tension-type headache (CTTH) and 19 healthy, age- and sex-matched controls. Intramuscular electrical stimuli (single and train of five pulses delivered at 2 Hz) were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…For this purpose, a verbal rating scale (VRS) was used: 0 = no change (in sensation); 1 = barely intense, no pain; 2 = intense, no pain; 3 = fairly intense, but no pain; 4 = slight pain (painthreshold); 5 = mild pain; 6 = moderate pain; 7 = moderate-strong pain; 8 = strong pain; 9 = severe pain; 10 = unbearable pain (Buchgreitz et al 2008). …”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, a verbal rating scale (VRS) was used: 0 = no change (in sensation); 1 = barely intense, no pain; 2 = intense, no pain; 3 = fairly intense, but no pain; 4 = slight pain (painthreshold); 5 = mild pain; 6 = moderate pain; 7 = moderate-strong pain; 8 = strong pain; 9 = severe pain; 10 = unbearable pain (Buchgreitz et al 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Decreased antinociceptive activity from supraspinal structures (ie, deficient descending inhibition) also may contribute to the increased pain sensitivity in chronic TTH [46,48,51,58,59]. Sandrini et al [48] demonstrated deficient diffuse noxious inhibitory control in chronic TTH, and a recent high-density brain electroencephalogram mapping study found impaired inhibition of nociceptive input in patients with chronic TTH [59].…”
Section: Decreased Antinociceptive Activitymentioning
confidence: 99%
“…Sandrini et al [48] demonstrated deficient diffuse noxious inhibitory control in chronic TTH, and a recent high-density brain electroencephalogram mapping study found impaired inhibition of nociceptive input in patients with chronic TTH [59]. Cathcart et al [51] recently reported deficient inhibition of repeated noxious mechanical stimulation in patients with chronic TTH.…”
Section: Decreased Antinociceptive Activitymentioning
confidence: 99%
“…10 It has been observed that central sensitization caused by prolonged periods of pain may lead to headache chronification. 11 Tension in suboccipital and neck muscles probably involves limitation of movement in the cervical region; and therefore, knowing the range of motion might be useful as a reference for the quality of neck muscles. The perception of pain and its different dimensions (ie, word descriptors for pain in headache) are aspects that should be assessed in patients with headache to better know the pain sensation experienced by the patient, as this can alter their quality of life.…”
Section: Introductionmentioning
confidence: 99%